Penerapan Algoritma Start-Step-Stop Code Pada Kompresi File Audio - Berry Richard Ornos Sinambela; Muhammad Syahrizal; Kristian Siregar (STMIK Budi Darma, 2020)
The size of the audio data file has become something of great concern in the digital age. Problems that arise due to the large size of data include the wasteful storage media used, as well as more time in terms of data exchange, data transfer over the internet network is a big problem in Indonesia because download and upload speeds are very low. The concept of compression was born as a real solution to the problem of the amount of space needed to store WAV format audio. To solve the existing problem of the large audio files obtained in the WAV format, a compression technique is needed with the aim of reducing the size of the WAV format audio file. By compressing the audio file, it is hoped that it can save from the hard disk. Through the compression process of WAV audio files using the Start-Step-Stop Code algorithm, it is hoped that in the future this compression system can have a major effect on WAV format audio storage and can better protect storage space and it is also hoped that this algorithm can be used from other objects to be compressed.Keywords: Digital Audio, WAV, Compression, Start-Step-Stop Code